Alfabetização científica, ensino por investigação e o uso da literatuta na educação infantil - Barbosa, Nilziete Jesus Chaves (2025)
Scientific Literacy is considered an essential process in the formation of any individual, aiming to shape critical, reflective, and active citizens in society. Early childhood education is the first stage of Basic Education, with the main goal of the comprehensive development of children. In this school phase, Science Education has been standing out in promoting Scientific Literacy through different strategies. Thus, the aim of this research was to analyze the contributions of implementing an Investigative Teaching Sequence (ITS), integrated with children's literature, for the development of Scientific Literacy (SL) in 5- and 6-year-old children. The research was conducted at a municipal early childhood education school, using the story "The Lava of the Colorful Volcano" as a basis, in accordance with the objectives proposed by the National Common Curricular Base (BNCC) and the Municipal Curriculum. The study was carried out through a qualitative approach, using the content analysis methodology proposed by Bardin (2011). Data was collected during the application of the ITS, through image and sound recordings, and analyzed based on the SL indicators proposed by Pizarro (2014). The results showed that the ITS integrated with children's literature is an effective strategy for developing scientific literacy from early childhood education, as well as promoting curiosity and critical thinking. Skills such as hypothesis formulation, refutation, observation and description, as well as thought organization and evidence identification, were also observed in the children during the scientific literacy process. It is concluded that the integration between Science Education and children's literature is an effective and interdisciplinary approach that significantly contributes to the comprehensive development of children and strengthens scientific literacy from the early stages of Basic Education.